Penerapan Metode Progresif Terhadap Hasil Belajar Keterampilan Handspring di Alat Meja Lompat - Fegie Rizkia Mulyana; Ridwan Gumilar (JUARA : Jurnal Olahraga, 2020)
In the gymnastics learning II, a variety of obstacles are often experienced during the learning process. The issues consist of the difficulties of lecturers to deliver learning materials, students’ lack of understanding and processing the information during learning process that affect to their grade and learning outcomes of handspring skills on the vault. The purpose of this study is to improve student activities and learning outcomes and to increase in the application of progressive methods to the learning outcomes of handspring skills on the vault. The method used in this research is action research. The results of this action research are an increase in the quality of student learning outcomes. In the first cycle the percentage of mastery learning obtained 85% of this result is obtained because at this time it is still lacking in the second kite phase that still requires motion learning experience, the weakness of foot repulsion is greatly increased at the height of the kite and landing phase. In cycle II, there is an increase in the learning outcomes with a percentage of mastery learning 98%. This indicates that the method of progressive application gives meaning to the improvement in learning outcomes of handspring skills on the vault.